Analysis of the Application of Training Principles in the Coaching of Long Jump Techniques among Students of the Faculty of Sports Science, Universitas Negeri Medan - Abdul Harris Handoko; Boy Indrayana; Ahmad Muchlisin Natas Pasaribu (Attractive : Innovative Education Journal, 2026)
This study aims to analyze the implementation of training principles in the coaching of long jump techniques among students of the Faculty of Sports Science, Universitas Negeri Medan (UNIMED). The research adopts a descriptive qualitative design to explore the extent to which fundamental training principles specificity, overload, progression, individualization, variation, and recovery are applied during long jump coaching sessions. Data were gathered through observation, semi-structured interviews with student-athletes and coaches, and document analysis of training plans. The results indicate partial implementation of scientific training principles, particularly a strong focus on general physical conditioning rather than technical refinement. Coaches tend to emphasize repetitive practice without sufficient variation or progressive overload, while feedback mechanisms are inconsistently applied. The study highlights both theoretical and empirical gaps in the pedagogical integration of training principles within the higher education context. Recommendations are proposed to enhance the effectiveness of technique-oriented coaching by strengthening planning, evaluation, and athlete-centered approaches